Pengaruh Penambahan Gula Pasir Terhadap Kuat Lentur Beton Dengan Perendaman Air Laut - Muhammad Iqbal Sudano; Eko Walujodjati (International Forum of Researchers and Lecturers, 2023)
Innovations in concrete design continue to be made to obtain maximum strength. The granulated sugar can be an added ingredient that functions to inhibit the concrete setting time so it doesn't dry out too quickly. Use to delay concrete setting time (setting time) for example with hot weather conditions, or extend compaction time to avoid cold joints and avoid the impact of settlement when fresh concrete is carried out at the time of casting. As for the curing experiment/treatment of the concrete by immersion in seawater to find out how construction buildings on the seaside affect construction such as bridge abutments, pile caps or buildings on the coast that are submerged or exposed to sea water whether there is a decrease in the quality of making concrete blocks. The experiment was carried out by adding a variety of granulated sugar to the concrete mixture of 50 grams (2% by weight of water), 70 grams (3% by weight of water) and 100 grams (4% by weight of water) then all the samples were immersed in sea water. Based on the results of the flexural strength test of concrete after 28 days of age, the highest test results obtained for the flexural strength of concrete were the addition of 100 grams of granulated sugar worth 3.00 MPa for the second was the addition of 50 grams of granulated sugar worth 0.515 MPa and for the third was the addition of sugar sand 70 grams 0.454 Mpa. This composition cannot be said to have decreased due to immersion in sea water, because there is no proven comparison with immersion using ordinary water.